PELAKSANAAN PEMBANGUNAN DI DESA BANJAR NAN TIGO KECAMATAN INUMAN KABUPATEN KUANTAN SINGINGI TAHUN 2019-2020 - Sutrianika "; Auradian Marta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Village development is one of the big agendas to oversee the implementation of Law no. 6 of 2014 concerning villages which are carried out systematically, consistently and sustainably by means of facilitation, supervision and assistance. However, there are still many developments in Banjar Nan Tigo Village that have not been realized due to insufficient village fund budgets, very low community participation in development and all funds that were originally for development have been converted into direct cash assistance funds for the community, so that the implementation of development is hampered. In this case, it can be assessed that there are still many inadequate village roads, still in the form of dirt roads and gravel roads, thus hampering the flow of goods and services, uneven development resulting in social jealousy, lack of community participation and insufficient budget funds. Furthermore, the data collection techniques used were interviews and documentation, while the data sources used were primary sources obtained from the research location in the form of research informants and supported by secondary data, namely documents related to interviews and document studies. The research location is in Banjar Nan Tigo Village, Inuman District, Kuantan Singingi Regency. The results show that the implementation of development in the village of Banjar Nan Tigo, Inuman District, Kuantan Singingi Regency in 2019-2020 has been carried out with the Village Development Planning Stages, namely starting from preparing the medium village development plan RPJMDes and preparing an annual development plan called RKP Desa, implementing Village Development and Monitoring and supervising the results of the implementation of village development. The factors that hinder the implementation of development in the village of Banjar Nan Tigo are community participation in the implementation of village development, limited quality of human resources, village financial resources, technical problems and village governance. Keywords: Implementation, Development, Barriers